Melanoma in situ colonizing basal cell carcinoma: a case report and review of the literature - Silvia E. Mancebo; Michael A. Marchetti; Travis J. Hollmann; Ashfaq A. Marghoob; Klaus J. Busam; Allan C. Halpern (Mattioli1885, 2015)
Colonization of basal cell carcinoma (BCC) by melanoma cells is a unique and uncommonly reported cutaneous entity. We describe a bluish nodule on the left forearm found during routine skin cancer surveillance examination with suspicious dermatoscopic findings including central-blue-white veil, sparse atypical dots, and a surrounding pink vascular blush with focal irregular tan-brown pigmentation at the periphery. Histopathology demonstrated a pigmented BCC with an overlying and adjacent melanoma in situ (MIS), as well as colonization of the BCC nodule by melanoma cells. We performed a review of the literature on the topic and discuss other presentations of cutaneous neoplasms composed of both BCC and melanoma, including collision, combined, and biphenotypic tumors. The prognostic and management challenges inherent to this distinctive neoplasm are summarized.